Spatiotemporal characteristics and influencing factors of China’s knowledge spillover network of the marine industry - Kai Liu; Kai Liu; Yi Zhang; Fei Peng; Fei Peng; Tong Xie; Qiang Du; Jia-yin Tan (Frontiers in Marine Science)
Using social network analysis, spatial econometric method and structural equation model, based on the patent citation data of China’s marine industry from 2008 to 2019, this paper analyzes the temporal-spatial characteristics and influencing factors of knowledge spillover network of marine Industry in China. The results show that: the knowledge spillover network with Qingdao, Beijing and Shanghai as the main distribution centers has expanded rapidly, and the network status of Zhoushan, Wuhan and other cities has improved significantly. The network space structure tends to be multi-core and complex, extending from coast to inland; There are significant differences in cyberspace. The central and western regions are low value areas, while the eastern region is the core area, and the core cities have built an “X” shaped spatial structure with Qingdao as the intersection; Knowledge proximity, social proximity, cognitive proximity and economic proximity are important factors that affect knowledge spillover networks. Geographic proximity has a reinforcing effect on knowledge proximity and economic proximity. This paper is beneficial in that it provides a reference and experience for the innovation of the marine industry and the high-quality development of the marine economy by effectively analyzing the spatio-temporal characteristics and influencing factors of China’s marine knowledge diffusion network.